ELECTRONIC COMMERCE DEVELOPMENT TRENDS IN KAZAKHSTAN - Amerkhanova A. B. (Academic Journal of Physical and Chemical Sciences, 2020)
In the process of rapid development of information technology and the active use of the Internet for commercial purposes, there is a transformation of the trading system. The active development of information technologies and the Internet creates a fundamentally new environment for business development: the formation of new markets, the emergence of demand for new goods and services, the creation of fundamentally new offers. The widespread use of information technology, along with globalization, is the factor that determines the nature of the development of the modern economy and the problems that need to be studied in the new conditions. Such new phenomena include the development of electronic business, in particular electronic commerce. Online stores are increasingly being crowded out globally. However, despite the fact that traditional retail purchases, since it has proven itself in a large number of consumers in its developed countries, e-commerce is still at an early stage of development in emerging markets, so it is necessary to disclose what factors contribute to its development. The rapid development of electronic sales of consumer goods in the Republic of Kazakhstan indicates an increase in the number of online stores with a wide range of goods and services. E-commerce in the Republic of Kazakhstan today is one of the most dynamically developing sales formats: the number of Internet users is growing, as well as the number of online store customers. Already today, the contribution of e-commerce to the economy of Kazakhstan is very significant, therefore, it is necessary to take a balanced approach to the regulation of this sphere. The article explores the main types and models of e-commerce in Kazakhstan. The main factors that influence the processes of the formation of a modern economy, which is more based on the automation of the basic routine operations of buying, selling and providing services to such aggregated economic entities as households, business, banking and the state, are determined and analyzed.